Resistive random access memory material based on natural product aggregation-induced molecule and polyacid compounding, and preparation method and application thereof

By using natural product-based aggregation-induced molecule and polyacid composite, the problem of poor morphology and poor repeatability in the manufacturing process is solved, and multi-stage controlled memory storage performance and high temperature stability are achieved, which is suitable for industrial production.

CN119654058APending Publication Date: 2025-03-18FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771559.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the manufacturing process, existing storage materials often face problems such as poor device morphology, poor repeatability, and complex synthesis process, which are difficult to meet the needs of high-density data storage.

Method used

Using a variable-resistant storage material based on the aggregation-induced molecule and polyacid composite of natural product-like aggregation is used to prepare berberine and H4[Si(W3O10)4]·26H2O as raw materials, using the hot solvent method, which simplifies the process flow and reduces environmental pollution.

Benefits of technology

The prepared material has multi-stage controlled memory storage performance, is suitable for multi-stage memristors, exhibits good cyclic fatigue and high temperature stability, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654058A_ABST
    Figure CN119654058A_ABST
Patent Text Reader

Abstract

The invention discloses a resistive random access memory material based on natural product aggregation-induced emission molecule and polyacid compounding and a preparation method and application thereof.The method comprises the specific preparation processes that a mixture of 0.1 mmol of natural product aggregation-induced emission molecules and 0.05 mmol of Keggin polyacid is dissolved in 10 mL of methyl alcohol, stirring is conducted for 2 h, stirring is conducted for 2 h, and then the mixture is cooled to the room temperature to obtain the resistive random access memory material based on natural product aggregation-induced emission molecule and polyacid compounding. The preparation method comprises the following steps: adding the raw materials into a 25mL stainless steel reaction kettle with a polytetrafluoroethylene lining, reacting at 160 DEG C for 3 days, cooling to obtain yellow red blocky crystals, and filtering, washing and drying to obtain the resistive random access memory material based on natural product aggregation-induced molecules and polyacid compounding. The method is simple and easy to operate, raw materials are easy to obtain and easy to implement, no harmful product is generated in the preparation process, environment-friendly green synthesis is achieved, and the multi-stage controllable memory storage material is prepared and can be applied to multi-stage memristors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of storage materials, and in particular relates to a resistive switching storage material based on a composite of natural product-type aggregation-inducing molecules and polyacids, and a preparation method and application thereof. Background Art

[0002] The era of rapid expansion of information has put forward higher requirements for the next generation of high-density data storage, and multi-level memory is the most practical way to break through the von Neumann bottleneck. In order to achieve high-density data storage, it is crucial to study new materials. Since organic-inorganic hybrid materials have a controllable structure, the resistance switching behavior can be significantly enhanced through subtle structural modifications and designs. However, it also has certain limitations. The manufacturing process of the device often faces problems such as poor device morphology, poor repeatability, and complex synthesis process. At present, there is an urgent need to develop new storage materials to meet practical needs. Summary of the invention

[0003] In order to solve the above problems, the present invention proposes a resistive switching memory material based on a composite of natural product aggregation-inducing molecules and polyacids, and a preparation method and application thereof. The method uses berberine (BBR) and H 4 [Si(W 3 O 10 ) 4 ]·xH 2 O is used as raw material and a hot solvent method is adopted. The preparation method is simple and easy to operate, the raw materials are easily available and easy to implement, and there are no harmful products in the preparation process. It is an environmentally friendly green synthesis. The prepared resistive memory material based on natural product-like aggregation-inducing molecules and polyacid composites is a multi-level controllable memory storage material, which can be used in multi-level memristors.

[0004] The present invention adopts the following technical solutions:

[0005] A method for preparing a resistive memory material based on a composite of natural product-type aggregation-inducing molecules and polyacids, the specific preparation process is: dissolving a mixture of 0.1mmol of natural product-type aggregation-induced emission molecules and 0.05mmol of Keggin polyacid in 10mL of methanol, stirring for 2h, adding into a 25mL stainless steel reactor lined with polytetrafluoroethylene, reacting at 160°C for 3 days, and obtaining yellow-red block crystals after cooling, filtering, washing and drying to obtain a resistive memory material based on a composite of natural product-type aggregation-inducing molecules and polyacids.

[0006] Preferably, the natural product-based aggregation-induced emission molecule is berberine; the Keggin polyacid is H 4 [Si(W 3 O 10 ) 4 ]·26H2 O.

[0007] Preferably, the cooling process is: cooling the polytetrafluoroethylene stainless steel reactor to room temperature at a rate of 5.4°C / h.

[0008] Preferably, the washing reagents are ethanol and distilled water; and the drying is performed by vacuum drying at a temperature of 40°C.

[0009] A resistive switching memory material based on a composite of natural product-type aggregation-inducing molecules and polyacids is prepared by the method for preparing a resistive switching memory material based on a composite of natural product-type aggregation-inducing molecules and polyacids.

[0010] An application of a resistive memory material based on a composite of natural product-type aggregation-inducing molecules and polyacids. The resistive memory material based on a composite of natural product-type aggregation-inducing molecules and polyacids is used as a resistive memory layer and is applied to a multi-level memristor.

[0011] Preferably, the structure of the multi-level memristor is a sandwich structure consisting of a bottom electrode, a resistive storage layer and a top electrode; the bottom electrode is a fluorine-doped indium tin oxide conductive material; and the top electrode is an inert metal material.

[0012] After adopting the above technical solution, the present invention has the following advantages compared with the background technology:

[0013] 1. The present invention is based on aggregation-inducing molecules (AIE) with aggregation-induced current effect and polyoxometalate molecules (POM) with redox properties and high temperature resistance, and prepares a resistive storage material based on a composite of natural product-type aggregation-inducing molecules and polyacids, which is a multi-level switch controllable storage material.

[0014] 2. The present invention uses berberine (BBR) and H 4 [Si(W 3 O 10 ) 4 ]·26H 2 O is used as raw material and a hot solvent method is adopted. The preparation method is simple and easy to operate, the raw materials are easily available and easy to implement, and there are no harmful products in the preparation process. It is an environmentally friendly green synthesis with low synthesis cost and excellent film-forming property. It is suitable for large-scale industrial production and has good application prospects. The prepared resistive memory material based on natural product-like aggregation-inducing molecules and polyacid composite is a multi-level controllable memory storage material, which can be used in multi-level memristors.

[0015] 3. The resistive memory material based on natural product aggregation-inducing molecules and polyacid composite of the present invention can form a uniform and dense film on the substrate, showing excellent multi-level memory storage performance at room temperature and high temperature conditions, and has good cycle fatigue resistance. The FTO / resistive memory material based on natural product aggregation-inducing molecules and polyacid composite / Ag device exhibits typical non-volatile WORM ternary storage characteristics at room temperature, and its ON2 / ON1 / OFF state current ratio is 10 5.3 :10 3.6 :1,V Set1 / V Set2 At 370℃, the device storage behavior shows typical non-volatile WORM ternary storage characteristics, and the ON2 / ON1 / OFF state current ratio is 10 5.0 :10 3.2 :1,V Set1 / V Set2 The device was tested at 370℃ and returned to room temperature. The device still showed typical ternary storage characteristics, which verified that the memory device has good device stability and provided a new strategy for the preparation of high-performance memory with high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The crystal structure diagram of the resistive switching memory material based on the natural product aggregation-inducing molecule and polyacid composite of the present invention.

[0017] Figure 2 This is an X-ray powder diffraction pattern of the resistive memory material based on a composite of natural product-based aggregation-inducing molecules and polyacids of the present invention.

[0018] Figure 3 This is the infrared spectrum of the resistive storage material based on the natural product aggregation-inducing molecule and polyacid composite of the present invention.

[0019] Figure 4 This is a liquid ultraviolet-visible diffuse reflectance spectrum of the resistive switching memory material based on the natural product-based aggregation-inducing molecules and polyacid composite of the present invention.

[0020] Figure 5 This is a thermogravimetric diagram of the resistive switching memory material based on a composite of natural product-based aggregation-inducing molecules and polyacids according to the present invention.

[0021] Figure 6 The present invention is a schematic diagram of the preparation process of a resistive memory material device based on a composite of natural product-based aggregation-inducing molecules and polyacids.

[0022] Figure 7This is a test diagram of the IV characteristic curve of the resistive switching memory material device based on the natural product aggregation-inducing molecule and polyacid composite at room temperature of the present invention.

[0023] Figure 8 This is a test diagram of the IV characteristic curve of the resistive memory material device based on the natural product aggregation-inducing molecule and polyacid composite at 370°C of the present invention.

[0024] Fig. 9 This is a test diagram of the IV characteristic curve of the resistive switching memory material device based on the natural product aggregation-inducing molecule and polyacid composite of the present invention when the high temperature returns to room temperature. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0026] See also Figures 1 to 9 .

[0027] Preparation of a resistive switching memory material based on a natural product-based aggregation-inducing molecule and a polyacid composite:

[0028] Berberine BBR (0.0408 g, 0.1 mmol) and H 4 [Si(W 3 O 10 ) 4 ]·26H 2 O (0.144 g, 0.05 mmol) was dissolved in 10 mL of methanol, and the mixture was stirred at room temperature for 2 h, then added into a 25 mL stainless steel reactor lined with polytetrafluoroethylene, and reacted at a reaction temperature of 160 ° C for 3 days. The polytetrafluoroethylene stainless steel reactor was cooled to room temperature at a rate of 5.4 ° C / h to obtain yellow-red block crystals, which were washed with ethanol and water to obtain 0.0518 g of product (the yield was 29.2%, calculated based on W), that is, a resistive storage material based on a composite of natural product-like aggregation-inducing molecules and polyacids was obtained.

[0029] First, place the FTO conductive glass in a beaker and add acetone, ethanol and deionized water in turn, and perform ultrasound for 20 minutes respectively. Use an oven drying at 100°C for 30 minutes to dry the FTO (20mm×20mm). Secondly, add the crystal to be tested (5mg) to DMF (10mL), and form a clear solution after ultrasound for 2h. Then take 0.2mL of the solution and drop it on the conductive surface of the conductive glass. Spin coating at 1000rpm, 3000rpm and 5000rpm for 10s respectively, and then anneal at 60°C for 3h to remove the DMF solution. Finally, use 0.5mg·mL -1 The top silver electrodes of all devices were prepared by passing a Ag nanowire suspension of 20% concentration through a mask with small circular holes of about 0.1 cm in diameter for 1 min, and the prepared devices were placed in an oven at 60°C for 30 min to improve their adhesion.

[0030] Performance Test:

[0031] 1. Crystal structure of resistive switching memory materials based on natural product-based aggregation-inducing molecules and polyacid composites Figure 1 As shown. Figure 1 It can be seen that the structural analysis of the resistive switching memory material based on the natural product aggregation-inducing molecule and the polyacid composite shows that the compound is composed of two parts: one (SiW 12 O 26 ) 3- Anion, two (C 20 H 18 O 4 N) + The polyoxometalate anion forms a zero-dimensional molecule with two organic cations through electrostatic attraction, belonging to the triclinic P-1 space group. The center of the silicotungstate anion is a heteroatom SiO 4 Tetrahedral configuration, ligand atoms are WO 6 The three octahedrons form a trimetallic cluster W by sharing oxygen atoms. 3 O 10 , four trimetallic clusters are connected corner-to-corner with the tetrahedron center, The length is within the normal range. The angle between the isoquinoline in berberine and the adjacent benzene ring plane is 19.46°. There is no coplanarity and some distortion. It is distributed in (SiW 12 O 26 ) 3- Both sides of the anion (such as Figure 1 Part a in the figure). 3D stacking diagram of resistive switching memory materials based on natural product-like aggregation-inducing molecules and polyacid composites, such as Figure 1Table 1 shows the crystallographic data and structural refinement parameters of the resistive switching memory material based on the natural product-like aggregation-inducing molecule and the polyacid composite.

[0032] Table 1: Crystallographic data and structural refinement parameters of resistive memory materials based on natural product-like aggregation-inducing molecules and polyacid composites

[0033]

[0034]

[0035] 2. X-ray powder diffraction analysis

[0036] like Figure 2 As shown, the X-ray powder diffraction spectrum of the resistive memory material based on the natural product-type aggregation-inducing molecules and polyacid composites, the experimental value and the fitting value are consistent, the results show that the compound is a pure phase, and the difference in intensity of some diffraction peaks is caused by the coarseness and anisotropy of the crystal grinding.

[0037] 3. Infrared spectrum characterization:

[0038] like Figure 3 As shown in the figure, the infrared spectra of the resistive switching memory material based on the natural product aggregation-inducing molecule and the polyacid composite. Since the organic parts of the three compounds are mainly berberine, and the inorganic parts are silicotungstate anions. In the infrared spectrum, the -1 The stretching vibration of the CN bond is at 1000-500cm -1 The vibration peaks in the region are attributed to the Mo-O asymmetric stretching vibration in the phosphomolybdic acid anion and the WO asymmetric stretching vibration in the phosphotungstate anion. The main infrared peak positions and their attributions of the resistive switching memory material based on the natural product-like aggregation-inducing molecules and polyacid composites are shown in Table 2.

[0039] Table 2: Main infrared spectral characteristic absorption peaks and their attributions of resistive memory materials based on natural product aggregation-inducing molecules and polyacid composites

[0040]

[0041] 4. Liquid UV diffuse reflectance spectroscopy analysis

[0042] The three compounds were tested for liquid UV-visible diffuse reflectance spectra in the wavelength range of 200-800nm. Figure 4The characteristic anion at 265 nm is attributed to the charge displacement transition of OW in the POM anion structure, the absorbance at 340 nm corresponds to the π~π* transition of the isoquinoline structure of berberine, and the absorption peak band near 425 nm comes from the n~π* transition of berberine.

[0043] 5. Thermogravimetric analysis

[0044] like Figure 5 As shown, in a nitrogen atmosphere, the heating rate was 10°C / min, the test temperature range was 30-800°C, and the compound was subjected to thermogravimetric testing. The test results are shown in Figure 5 As shown. The crystal structure of the resistive switching memory material based on natural product aggregation-inducing molecules and polyacid composites can be maintained up to 370°C. In the first stage of heating (30-370°C), the weight loss ratio is 1.01% (theoretical value is 0.87%), which is attributed to the loss of the methyl group of the berberine part in the crystal. The weight loss ratio in the second stage from 270 to 600°C is 10.20% (theoretical value is 10.99%), which is attributed to the loss of a single organic ligand. The weight loss ratio in the third stage from 600 to 800°C is 17.87% (theoretical value is 21.93%), which is mainly attributed to the loss of two organic ligands in the compound.

[0045] 6. Multi-level controllable memory storage performance test:

[0046] The IV characteristic curves of FTO / resistive switching memory material based on natural product aggregation-inducing molecules and polyacid composites / Ag devices were tested in a KEYSIGHT-B2901A single-channel semiconductor parameter tester.

[0047] like Figure 7 The figure shows the electrical characteristics of FTO / resistive switching memory material based on natural product aggregation-inducing molecules and polyacid composite / Ag at room temperature. Under 0.5A limiting current (CC), the FTO / resistive switching memory material based on natural product aggregation-inducing molecules and polyacid composite / Ag memory device was tested for the current-voltage (IV) characteristic curve of 0V→5V→0V→-5V. Figure 7 As can be seen in part a, when a forward sweep voltage (from 0 to 5.0 V) is applied, the device is initially in a low conductivity (“0” or “off”) state. When the forward voltage is increased to 1.14 V, the device switches from a low conductivity (~10 -7.4 A, "off" state) to medium conductivity (~10 -3.7 A, "ON1" state). Later, when the applied forward voltage is increased to 1.49 V, the "ON1" state switches to a high conductivity state (~10 -2.1A, "ON2" state). The process of low conductivity to medium conductivity and then to high conductivity is equivalent to the "write" process in digital storage. In the subsequent 5-0V and 0-5V scans, the device remains stable in the high conductivity state, which is equivalent to the "read" process in digital storage. For the ON2, ON1, and OFF states, the corresponding current ratio is 10 5.3 :10 3.6 :1, higher than covalent organic polymer: ITO / Py-COPs / Ag (ON2 / ON1 / OFF=10 3.1 :10 0.6 :1), graphene oxide-based memory: Al / PVK-AZO-GO / ITO (ON2 / ON1 / OFF=10 4.5 :10 1.6 / 1), which means the device exhibits typical non-volatile WORM ternary storage characteristics. Figure 7 It can be seen from part b that at constant voltages of 0.01V, 1.19V, and 1.84V, ON2, ON1, and OFF have good stability and no obvious deviation occurs. Figure 7 Part c performs V on 10 rounds of measurement data. Set1 and V Set2 The statistics are made into a bar graph based on the distribution characteristics. The results show that the ternary storage performance of the device has good repeatability. Figure 7 As shown in part d, 10 random IV characteristic curves are used to make a waterfall diagram to verify the ternary storage stability of the device. Figure 7 Part e shows that the stability of the memory device is further verified by taking 100 cycles of high and low resistance currents at 0.01V and making them into a scatter plot. And through the statistical results of 100 cycles of IV characteristic curves, the ternary yield of the device is 70%, which is higher than other biocompatible ternary memories, such as tannic acid and iron complex devices: ITO / TA-Fe III / Al(53%). Retention time is a key parameter for device stability, such as Figure 7 As shown in the middle f part, under the 0.1V constant voltage, the device is in the "OFF", "ON1", and "ON2" states for 3×10 3 s did not change significantly, and the results showed that the device had good stability.

[0048] like Figure 8 The figure shows the electrical characteristics of FTO / resistive switching memory material based on natural product aggregation-inducing molecules and polyacid composite / Ag at 370°C. The current-voltage (IV) characteristic curve test of FTO / resistive switching memory material based on natural product aggregation-inducing molecules and polyacid composite / Ag memory device under 0.5A limiting current (CC). Figure 8 As can be seen in part a, when a forward sweep voltage (from 0 to 5.0 V) is applied, the device is initially in a low conductivity (“0” or “off”) state. When the forward voltage is increased to 0.89 V, the device switches from a low conductivity (~10 -6.7 A, "off" state) to medium conductivity (~10 -3.6 A, "ON1" state). Later, when the applied forward voltage is increased to 1.12V, the "ON1" state switches to a high conductivity state (~10 -1.9 A, "ON2" state). This process is equivalent to the "write" process in digital storage. In the subsequent 5-0V and 0-5V scans, the device remains stable in the high conductivity state, which is equivalent to the "read" process in digital storage. For the ON2, ON1, and OFF states, the corresponding current ratio is 10 4.8 :10 3.1 :1, indicating that the device exhibits typical non-volatile WORM ternary storage characteristics. Figure 8 It can be seen from part b that at constant voltages of 0.01V, 1.04V and 1.64V, ON2, ON1 and OFF have good stability and no obvious deviation occurs. Figure 8 Part c performs V on 10 rounds of measurement data. Set1 and V Set2 The statistics are made into a bar graph based on the distribution characteristics. The results show that the ternary storage performance of the device has good repeatability. Figure 8 As shown in part d, 10 random IV characteristic curves are used to make a waterfall diagram to verify the ternary storage stability of the device. Figure 8 The stability of the memory device is further verified by taking 100 cycles of high and low resistance state current distribution scatter plots at 0.01V as shown in part e. The device can withstand much higher temperatures than devices made of other biocompatible materials, such as biogelatin memory: Ag / gelatin / Ag / GP (70°C). The results show that the device can operate stably at 370°C. Figure 8 The device shown in part f can achieve a maximum on / off ratio of 10 at a high temperature of 370°C. 3 .

[0049] like Fig. 9The figure shows the electrical characteristics analysis of FTO / resistive memory material based on natural product aggregation-inducing molecules and polyacid composite / Ag from 370℃ back to room temperature. The current-voltage (IV) characteristic curve test of FTO / resistive memory material based on natural product aggregation-inducing molecules and polyacid composite / Ag memory device under 0.5A limiting current (CC). It can be observed from the figure that the device exhibits typical ternary memory characteristics at 370℃, and when the ambient temperature is restored to room temperature, the device can still exhibit typical ternary memory characteristics, and repeat three cycles to verify the high-temperature storage stability of the device, and it is found that the device has good high-temperature resistance and can withstand high temperatures of 370℃.

[0050] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a resistive switching memory material based on a composite of natural product aggregation-inducing molecules and polyacids, characterized in that: The specific preparation process is: dissolve a mixture of 0.1 mmol of natural product-type aggregation-induced emission molecules and 0.05 mmol of Keggin polyacid in 10 mL of methanol, stir for 2 hours, add it into a 25 mL stainless steel reactor lined with polytetrafluoroethylene, and react at 160°C for 3 days. After cooling, yellow-red block crystals are obtained. After filtration, washing and drying, a resistive storage material based on a composite of natural product-type aggregation-inducing molecules and polyacids is obtained.

2. The method for preparing a resistive switching memory material based on a composite of natural product aggregation-inducing molecules and polyacids as claimed in claim 1, characterized in that: The natural product aggregation-induced luminescence molecule is berberine; the Keggin polyacid is H4[Si(W3O 10 )4]·26H2O.

3. The method for preparing a resistive switching memory material based on a composite of natural product aggregation-inducing molecules and polyacids as claimed in claim 1, characterized in that: The cooling process is as follows: cooling the polytetrafluoroethylene stainless steel reactor to room temperature at a rate of 5.4°C / h.

4. The method for preparing a resistive switching memory material based on a composite of natural product aggregation-inducing molecules and polyacids as claimed in claim 1, characterized in that: The washing reagents are ethanol and distilled water; the drying is vacuum drying at a temperature of 40°C.

5. A resistive switching memory material based on a natural product aggregation-inducing molecule and a polyacid composite, characterized in that: The resistive switching memory material based on a composite of natural product-based aggregation-inducing molecules and polyacids is prepared by the method for preparing a resistive switching memory material based on a composite of natural product-based aggregation-inducing molecules and polyacids as described in any one of claims 1 to 4.

6. An application of the resistive switching memory material based on the natural product aggregation-inducing molecule and polyacid composite as claimed in claim 5, characterized in that: The resistive memory material based on the natural product aggregation-inducing molecule and the polyacid composite is used as a resistive memory layer and is applied to a multi-level memristor.

7. The use of a resistive switching memory material based on a composite of a natural product aggregation-inducing molecule and a polyacid as claimed in claim 6, characterized in that: The structure of the multi-level memristor is a sandwich structure consisting of a bottom electrode, a resistive storage layer and a top electrode; the bottom electrode is a fluorine-doped indium tin oxide conductive material; and the top electrode is an inert metal material.